Iceland 2024 - Eygló Svala Arnarsdóttir; Averbuck, Alexis, 1972-; Egill Bjarnason; Thiruvengadam, Meena (Lonely Planet guidebooks., 2024)
Lonely Planet's Iceland is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Drive the Ring Road, glimpse the northern lights, and swim in the Blue Lagoon; all with your trusted travel companion.